2020
DOI: 10.1111/1462-2920.15131
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an extracytoplasmic function sigma factor that facilitates c‐type cytochrome maturation and current generation under electrolyte‐flow conditions in Shewanella oneidensisMR‐1

Abstract: Shewanella oneidensis MR-1 was cultured on electrodes in electrochemical flow cells (EFCs), and transcriptome profiles of electrode-attached cells grown under electrolyte-flow conditions were compared with those under static (nonflow) conditions. Results revealed that, along with genes related to c-type cytochrome maturation (e.g., dsbD), the SO_3096 gene encoding a putative extracytoplasmic function (ECF) sigma factor was significantly upregulated under electrolyte-flow conditions. Compared to wild-type MR-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…More recently, refute of the protein's involvement in metal ion tolerance has led to predictions of CutA1 proteins acting in a small molecule carrier or signaling capacity [154,155]. Still, the functions of all three "CutA" proteins remain under-defined with only small attributions put forward for each, in addition to CutA1: CutA2 (DsbD) is thought to have disulfide oxidoreductase activity [156]; and CutA3 (YjdC) has been annotated as an HTH-type transcriptional regulator (TetR/AcrR family), more specifically a negative regulator of nitroreductase NfnB [157]. S5 for categories and respective COG designations/InterPro signature profiles in tabular format.…”
Section: The Duf34 Family Can Be Split Into Eight Interconnected Subgroupsmentioning
confidence: 99%
“…More recently, refute of the protein's involvement in metal ion tolerance has led to predictions of CutA1 proteins acting in a small molecule carrier or signaling capacity [154,155]. Still, the functions of all three "CutA" proteins remain under-defined with only small attributions put forward for each, in addition to CutA1: CutA2 (DsbD) is thought to have disulfide oxidoreductase activity [156]; and CutA3 (YjdC) has been annotated as an HTH-type transcriptional regulator (TetR/AcrR family), more specifically a negative regulator of nitroreductase NfnB [157]. S5 for categories and respective COG designations/InterPro signature profiles in tabular format.…”
Section: The Duf34 Family Can Be Split Into Eight Interconnected Subgroupsmentioning
confidence: 99%
“…It is also noteworthy that an MR-1 mutant that does not synthesize cell-surface polysaccharides is more adhesive to electrodes than the wildtype and generates more current [50]. A recent work has conducted transcriptomic analyses of EABFs for gaining insights into molecular mechanisms behind EABF formation by MR-1 under electrolyte-flow conditions, suggesting the involvement of several yet-unidentified global regulators, including those categorized into an extracytoplasmic function sigma factor and a diguanylate synthase [51]. A subsequent study has shown that the diguanylate synthase is involved in regulating the global level of cyclic-di-GMP (c-di-GMP) in MR-1 cells and facilitating biofilm formation on electrodes [52].…”
Section: Biofilm Formation For Electrochemical Interactions With Elecmentioning
confidence: 99%
“…More recently, refute of the protein's involvement in metal ion tolerance has led to predictions of CutA1 proteins acting in a small molecule carrier or signaling capacity [155,156]. Still, the functions of all three "CutA" proteins remain under-defined with only small attributions put forward for each, in addition to CutA1: CutA2 (DsbD) is thought to have disulfide oxidoreductase activity [157]; and CutA3 (YjdC) has been annotated as an HTH-type transcriptional regulator (TetR/AcrR family), more specifically a negative regulator of nitroreductase NfnB [158]. clade of Viridiplantae with the closest incidence of homologs occurring in select haptophyta.…”
Section: A Variable Central Insertion Occurs In Some Duf34 Family Membersmentioning
confidence: 99%